Sovereign Wealth Funds 2019 - Capapé, Javier (IE University, 2020)
In 2019, the growth of the world economy slowed to 2.9%, the lowest annual rate recorded since the subprime crisis. This was a year in which the elements of uncertainty that had previously threatened the stability of the cycle began to have a more serious effect on economic expansion. Among these elements, there are essentially two – both of a political nature – that stand out from the rest. The first is the trade war between the world’s leading economy, United States and its nearest contender, China, which led to a dangerous tariff escalation. The second was the confirmation of the United Kingdom’s withdrawal from the European Union, whose long denouement plunged the economy and the companies of the old continent into uncertainty. However, the negative impact of both these factors is clearly waning, and, coupled with the continued favorable financial conditions, suggests a return to growth of the world economy of 3.3% for 2020 and 3.4% for 2021.
Keywords: Sovereign wealth funds; Fondos de capital soberanos; Economic growth; Crecimiento económico; Politics; Políticas; Trade; Comercio